1993
DOI: 10.1111/j.1365-2427.1993.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of allelopathic effects of Daphnia

Abstract: 1. The hypothesis is tested that large daphnids are able to suppress their own and other spedes' feeding and reproduction by means of excreting an inhibitory chenucal (or chemicals). 2. In laboratory experiments with an Australian spedes, Daphnia carinata, water preconditioned with 3-67 daphnids I"' for 30 h had the effect of redudng feeding rates of D. carinata and D. lumholtzi provided with Selenastrum capricornutum. 3. For the two Daphnia spedes, there were highly significant negative correlations between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 19 publications
8
68
1
Order By: Relevance
“…The former two observations suggest that daphnids experience crowded conditions as conditions of food stress, although they were fed the same amount of algae. Only a few studies have tried to disentangle the direct effect of crowding from food concentration effects in the laboratory (Seitz 1984;Guisande 1993;Matveev 1993;Goser and Ratte 1994;Burns 1995). With the exception of Seitz (1984), all of these authors reported the same pattern as found in our study: although food was abundant, animals reacted as if they were food limited.…”
Section: Discussionsupporting
confidence: 73%
“…The former two observations suggest that daphnids experience crowded conditions as conditions of food stress, although they were fed the same amount of algae. Only a few studies have tried to disentangle the direct effect of crowding from food concentration effects in the laboratory (Seitz 1984;Guisande 1993;Matveev 1993;Goser and Ratte 1994;Burns 1995). With the exception of Seitz (1984), all of these authors reported the same pattern as found in our study: although food was abundant, animals reacted as if they were food limited.…”
Section: Discussionsupporting
confidence: 73%
“…Crowding in laboratory populations of cladocerans and rotifers can affect feeding, growth, age at first reproduction, and fecundity. In many of these cases, the positive or negative effects of crowding are attributable to unidentified chemicals produced by the population (Seitz 1984;Helgen 1987;Matveev 1993;Goser and Ratte 1994;Burns 1995Burns , 2000Kirk 1998;Yoshinaga et al 1999;Mitchell and Carvalho 2002). In addition, crowding provides a stimulus for the initiation of bisexual reproduction in both Daphnia (Stross and Hill 1965) and Brachionus (Gilbert 1963a(Gilbert , 2002Hino and Hirano 1976;Snell and Boyer 1988).…”
mentioning
confidence: 99%
“…The chemicals responsible for affecting growth and fecundity in Daphnia operate across species (Seitz 1984;Burns 1995Burns , 2000, and water conditioned by Daphnia carinata inhibits feeding in conspecifics, Daphnia lumholtzi, Moina micrura, and Diaphanosoma unguiculatum (Matveev 1993). …”
mentioning
confidence: 99%
“…There is some evidence in the water flea Daphnia that chemicals are involved in habitat segregation between competing species. Infochemicals released from (intra-und interspecific) competitors affected a number of life history parameters of Daphnia pulex and Daphnia cucullata (Matveev 1993;Boersma et al 1999;Lü rling et al 2003), and Daphnia magna was found to avoid media, which had been inhabited by D. pulex (Roozen and Lü rling 2001).…”
Section: The Mechanism Of Interactive Habitat Segregationmentioning
confidence: 99%